Joining wood as a basic construction for furniture / Mohd Irwan Sukeri - Sukeri, Mohd Irwan (2001)
Joining wood is the important thing in furniture manufacturing industries. The elements and types of joints can influence joints wood must be depressed in furniture manufacturing. Also, the strength of joints depends on wood joints. Generally, joining wood is the base of furniture manufacturing that could produce unique and high technology furniture.